Additions and updated names for grasses of Durango, Mexico - Herrera-Arrieta, Yolanda (Instituto de Ecología, A.C., 2014)
Twelve years after publication of the floristic treatment “Las Gramíneas de Durango”, a list of accepted names is updated based on recent botanical work in Durango, Mexico. Ninety-one genera, 367 species, 15 subspecies, 55 varieties and 2 forms are included. Of these, 14 genera are newly recognized for Durango, whereas 17 genera previously reported from the state are now treated as synonyms, and three genera previously recorded are excluded. At the specific and infraspecific levels, 46 changes for synonymy occurred. Fifteen species were excluded, while 43 species and 27 infraspecific taxa were added. Four species are reported as new records for the state.